The Role of Institutional Capabilities In Achieving Work Quality within the International Monetary Fund - AL-Rajhi, Saja Abdulrahman; Aldakheel, Hiafa (The Arab Journal of Administration, 2024)
The study aimed to identify the role of institutional capabilities in achieving the quality of work within the International Monetary Fund and to achieve its objectives it used the descriptive analytical approach, and it followed two measures the first one is the measure of institutional capabilities represented by the independent variable with its dimensions (the cognitive dimension, the emotional dimension, the behavioral dimension), and the second one is the measure of work quality represented by the dependent variable. The statistical analysis program (spss) was used to analyze the data through the study’s questions and hypotheses, and the study sample was included of (166) male and female employees. The results showed that there is a role for institutional capabilities in achieving the quality of work, It was found that there was a statistically significant relationship at the level of statistical significance (0.05 ≥ α) for the cognitive dimension in achieving quality work within the International Monetary Fund, and there was no statistically significant relationship at the level of statistical significance (0.05 ≥ α) for the emotional dimension in achieving quality work within the Monetary Fund. There is no statistically significant relationship at the level of statistical significance (0.05 ≥ α) for the behavioral dimension in achieving work quality within the International Monetary Fund. The results show that there are no differences at the level of statistical significance at (0.05 ≥ α) in achieving work quality due to demographic variables ( gender, age, educational qualification, job level, years of experience) and this indicates that there is a great ability to select employees, as they all enjoy a high degree of quality at work, and the study recommended the importance of conducting more studies on institutional capabilities in achieving the quality of work within the International Monetary Fund and in many public institutions and the economic, health and social sectors, and the interest in applying this study to the various sectors that can benefit from it in the future.